An investigation into the cardiovascular effects of propofol and alfentanil for total intravenous anaesthesia - Coetzee, Johannes Francois (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.)__University of Stellenbosch, 1993.